A history of violence: magma incubation, timing and tephra distribution of the Los Chocoyos supereruption (Atitlán Caldera, Guatemala). (11th January 2021) - Cisneros de León, Alejandro; Schindlbeck‐Belo, Julie C.; Kutterolf, Steffen; Danišík, Martin; Schmitt, Axel K.; Freundt, Armin; Pérez, Wendy; Harvey, Janet C.; Wang, Kuo‐Lung; Lee, Hao‐Yang
ABSTRACT: The climactic Los Chocoyos (LCY) eruption from Atitlán caldera (Guatemala) is a key chronostratigraphic marker for the Quaternary period given the extensive distribution of its deposits that reached both the Pacific and Atlantic Oceans. Despite LCY tephra being an important marker horizon, a radioisotopic age for this eruption has remained elusive. Using zircon (U–Th)/He geochronology, we present the first radioisotopically determined eruption age for the LCY of 75 ± 2 ka. Additionally, the youngest zircon crystallization 238 U– 230 Th rim ages in their respective samples constrain eruption age maxima for two other tephra units that erupted from Atitlán caldera, W‐Fall (130 +16 /−14 ka) and I‐Fall eruptions (56 +8.2 /−7.7 ka), which under‐ and overlie LCY tephra, respectively. Moreover, rim and interior zircon dating and glass chemistry suggest that before eruption silicic magma was stored for >80 kyr, with magma accumulation peaking within ca . 35 kyr before the LCY eruption during which the system may have developed into a vertically zoned magma chamber. Based on an updated distribution of LCY pyroclastic deposits, a new conservatively estimated volume of 1220 ± 150 km 3 is obtained (volcanic explosivity index VEI > 8), which confirms the LCY eruption as the first‐ever recognized supereruption in Central America.